Weight cycling alters muscular strength and endurance, ratings of perceived exertion, and total body water in college wrestlers - Wenos, D. L.; Amato, H. K. (Perceptual and Motor Skills, 1998)
Weight cycling is the continued loss of body weight practiced by wrestlers to compete in a lower weight class. Effects of weight cycling on muscular strength, muscular endurance, total body water, and ratings of perceived exertion of the dominant hamstring-quadricep and shoulder girdle were examined in 19 wrestlers during a collegiate season. Over a 4.5-mo, period, total body water changes occurred only during acute dehydration. A decrease of > or = 3% of body weight over a 24-hr. period was classified as acute dehydration. Large muscle groups changed little in muscular strength and endurance whereas the smaller shoulder abductors and adductors and hamstring muscles were differentially affected at times of testing. Ratings of perceived exertion declined after the 4.5-mo. wrestling season of weight cycling but not at times of acute dehydration.